(untitled) (Czech Journal of Multidisciplinary Innovations, 2023)
In today’s world, the tourism trend has changed from mass to individualistic patterns and tourists give more priority to flexibility and meaningful experiences. Fundamental changes in the demand and supply side of tourism, as well as the creation of experience economy and knowledge-based economy models, in the macro space of economic development, have pushed tourism in the direction of creativity; So, it has led experts to believe that the sustainability of tourism is creative tourism. The purpose of this research is to investigate the status of creative tourism components in Al-Hindiya Dam its role in sustainable urban development. The current research is applied in terms of purpose and descriptive and analytical in terms of execution method. The statistical population of the research is made up of all the citizens of Al-Hindiya Dam, which according to the general housing census of 2015, there were 106,739 people, and using Cochran’s formula, 384 people were selected as the sample size. The research data was collected using a researcher-made questionnaire. The validity of the questionnaire has been confirmed using the opinions of professors and experts. Also, Cronbach’s alpha was used to obtain its reliability. The value of Cronbach’s alpha obtained is equal to 0.80, which shows that the questionnaire has the necessary validity to measure the research variables and is a desirable number. To analyze the findings of the research, one-sample t-test, multivariate regression analysis and Pearson’s correlation coefficient were used. The results of the T-Tech test showed that the financial index with an average of 3.78 is higher than the desired average, and the tourism indicators with an average of 2.73, the business index with an average of 2.66, and the learning and growth index with an average of 2.67 are lower than the situation. They are favorable. The results of multivariable regression showed that the financial variable had the greatest impact on sustainable urban development with a beta value of 0.371, and the tourism variable had the least impact with a beta value of 0.132